Mechanical properties of selected granitoids along the Karora hydropower project, Besham, Northern Pakistan: Insights from petrography and joint analysis - Khan, Musa; Li, Huan; Khan, Asad; Hussain, Waqas; Khan, Rehan; Ali, Rashid (Frontiers in Earth Science, 2023)
The stability of tunnel site depend upon the deformation behaviors of the surrounding rocks including joint density, mineral composition, micro cracks, grain boundaries etc. The aim of this study was to analyze the mechanical properties of Besham Complex, Northern Pakistan in terms of petrography, and joint analysis. The Besham complex is more prone to deformation as it is bounded by Main Mantle Thrust (MMT) in the north, Thakot fault (Tf) in the east, and swat block in the west. In the study area, the deformation are observed at mesoscopic scale while alteration in grains and fractures were determined at microscopic scale. The detail petrographic study of the representative samples from each station reveal that the area is dominantly composed of rocks ranging from granitic gneiss to amphibolite, while dolomitic marble was also observed in the outlet of the tunnel. Extensive field work was performed to determine the Joints Volume (JV), in which the number of joints per meter cube were recorded for each joint set, then through JV analysis the Rock Quality Designation (RQD) were calculated. The RQD value <25% suggested that the majority of rocks belongs to very poor quality, while others with RQD values ranges between 25-50% belongs to poor quality. Additionally, the petrographic analysis revealed that the dominant contents of the rock samples are feldspar (55.6%), quartz (27 %), and mica (17.4%). Furthermore, petrographic control over surface joints volume were established, which infer that abundant feldspar, coarse grain, anhedral to subhedral grain shape, microcracks and alteration of minerals provide planes of weakness for joints, thus, it reduces the value of RQD. Therefore, some serious precautions and supporting measurements are essential to avoid severe geo-hazard during further excavation.